Peran Zakat dan Pajak: Antara Kewajiban Agama dan Negara - Ishma Ramadani; Andi Mustaqfirah Aminuddin; Kurniati Kurniati (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Zakat and taxes are two obligations that must be fulfilled. This study starts from the question of whether zakat can replace taxes and how both contribute to public health. This study aims to analyze and expose it in a role to create the benefit and stability of the economy. In this study, using a qualitative approach, the method of library research through the review of books, scientific journals, and articles related to the theme discussed. This invention explains that zakat and taxes both have a foundation and legal provisions, but have the same goal to achieve the benefit and Shari'a. The study concluded that zakat and taxes cannot replace each other, but can collaborate so that zakat and taxes are managed properly, and increase awareness in the community.